The clinically applied PARP inhibitor talazoparib ameliorates imiquimod-induced psoriasis in mice without reducing skin inflammation - Molnár, Petra; Demény, Máté Ágoston; Várkonyi, Beáta; Polgár, Zsuzsanna; Pór, Ágnes; Kovács, Ilona; Szegedi, Andrea; Szöllősi, Attila Gábor; Szántó, Magdolna (Frontiers in Pharmacology, 2025)
BackgroundConsidering the role PARPs play in inflammation, we assessed the effect of PARP inhibition in an inflammatory skin condition, psoriasis, to explore novel avenues for the potential repurposing of PARP inhibitors that are currently used in tumour therapy.MethodsThe imiquimod (IMQ)-induced model of psoriasis was applied in BALB/c mice. Mice received daily intraperitoneal injection of either one of four PARP inhibitors or their vehicle prior to treatment of the shaved back skin of mice with IMQ-containing cream or control cream for four days. The appearance of the skin of mice was scored daily according to the extent of erythema, induration and scaling. The most effective PARP inhibitor was selected for detailed studies on mouse skin and in a human keratinocyte cell line.ResultsOf the PARP inhibitors, talazoparib and rucaparib improved the imiquimod-induced symptoms on mouse skin. Application of talazoparib in the psoriasis model resulted in maintained terminal differentiation and reduced proliferation of epidermal keratinocytes. Conversely, talazoparib also enhanced the production of pro-inflammatory chemokines in the skin of mice. These effects of talazoparib was associated with increased mitochondrial production of reactive oxygen species and a consequent activation of pro-apoptotic and pro-inflammatory pathways in keratinocytes.ConclusionPARP inhibition by talazoparib promotes terminal differentiation of epidermal keratinocytes that may be beneficial in psoriasis. Despite the fact that talazoparib exerted a pro-inflammatory effect in the skin, which is not unprecedented in anti-psoriatic therapy, these findings may advance the conduction of pre-clinical and clinical trials with PARP inhibitors in psoriasis management.